At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
whatcha need help with?
how do i solve this system: 5x+2y =7 -x/2 + y/6 = 3/2 i have been trying to solve this but can't get it right, could you show me the steps!
I did that one on your other post, do you see it?
solve for y in the top: y = -5x/2 +7/2 plug it into the bottom equation: -x/2 + (-5x/2 +7/2)/6 = 3/2 Solve for x: -x/2 -5x/12 +7/12 = 3/2 -6x/12 -5x/12 +7/12 = 18/12 -6x -5x +7 =18 -11x = 11 x=-1 Now that we have a solid number for x; plug it into the equation we found for y: y = -5(-1)/2 +7/2 y= 5/2 + 7/2 y= 12/2 = 6 Double check for accuracy :)
ok thanks i really appreciate it, i have one other... completing the square t^2 -9t_______ it says to first complete trinomial ____________________________ the then (_________________________)^2 bionomial squared...
for the first question... i was taught to plug 0 in.... how did you get 7/2 ....
Yes, to complete the square we need to find a term whose product adds up to (-9); which is just (-9/2)^2.
To solve for y: subtract (5x) from both sides: 2y = -5x + 7 now divide everything by (2): (2/2)y = (-5/2)x + (7/2) y = (-5/2)x + (7/2)
ok got that... and then this step confuses me Solve for x: -x/2 -5x/12 +7/12 = 3/2 -6x/12 -5x/12 +7/12 = 18/12
(t-(9/2))^2 = (t-(9/2)) (t-(9/2)) = t^2 -9 + 81/4
Solve for x: -x/2 -5x/12 +7/12 = 3/2 -6x/12 -5x/12 +7/12 = 18/12
got me lost...
it started out different...
with the 6 on the bottoms and turned to tweleve why did you multiply
To solve for x: we need to get all the fractions having the same denominators. The common denominator is 12: -x/2 needs to be multiplied by 6/6 to get a 12 on the bottom: -6x/12 -5x/12 already gots a 12 +7/12 already gots a 12 3/2 needs to be multiplied by 6/6 to get 12 on bottom: 18/12 Now because everything has a 12 on the bottom, we can toss the 12 out to clean up the equation: -6x -5x +7 = 18
but what happens to the 6 on the bottom of the 2nd fraction...
i see it: we solved for y to get: y = -5x/2 +7/2 The second equation has the term: y/6, so plug in what you found out about "y" to get: (-5x/2 +7/2)/6 when we divide the 6 thru we get: (-5x/2)/6 and (7/2)/6 the 6 actually multiplies to the bottom number, the 2. so that the denominators become 12. Does that make sense? I can try explaining it another way if you like
i am writting it down sorry its taking me so long.. i really appreciate your help :)
ok i understand that now, so then once i have those answers (-x/2) (-5x/2)/6 (7/2)/6 = 3/2 what am i doing to get twelve? becaues isn't (7/2)/6 technically .58
let me try it this way, cause fractions are terrible in this format. top: (-5x)(1) +(7)(1) = -5x +7 bottom: (2) (6) (2)(6) = 12 12 How does that look? :)
more confusing i have wrritting out fine... with the fractions over 6 but don't get what i am doing if i have 7/2 over 6 that equals .58
To divide fractions; flip the bottom one over and multiply across. (7/2)/(6/1) is the same as (7/2)(1/6) = (7/12)
gotta run; have fun :)